A clinical study of Punarnava Mandura in the management of Pandu Roga in old age (geriatric anemia) - Pandya, Megha G. (Ayu, 2014)
BACKGROUND: The incidence of anemia rises with age. The consequences of anemia are many and serious, affecting not only individual's health, but also the development of societies and countries. Pandu Roga can be effectively compared with anemia on the ground of its similar signs and symptoms. AIM: To evaluate the Panduhara and Rasayana effect of Punarnava Mandura in the management of Pandu Roga in old age (geriatric anemia). MATERIALS AND METHODS: The study was conducted in 50 clinically diagnosed patients of geriatric anemia. Patients were treated with Punarnava Mandura 2 tablets (250 mg each) twice in a day after lunch and dinner with Takra (butter milk) for 90 days. Among 50 registered patients, 40 patients had completed the treatment and 10 patients discontinued the treatment. Results were analyzed using Wilcoxon signed-rank test for subjective parameters and for assessment of objective parameters paired t-test was adopted. RESULTS: At the end of study, drug has shown beneficial effect in patients of anemia by providing highly significant result in chief complaints, associated symptoms, Kshaya of Dhatu and Agni Bala, Deha Bala and Sattwa Bala. It has also improved quality-of-life (QOL) of the patients. Moderate and mild improvement was observed in 30 and 70% of the patients respectively. CONCLUSION: Punarnava Mandura may work as Rasayana in geriatric anemia by providing highly significant results on clinical features of Pandu Roga, Dehabala, Agni Bala and Sattwa Bala and by improving QOL. of patients of geriatric anemia.